Incidencia de la comprensión lectora en el rendimiento escolar de los estudiantes de séptimo año de EGB de la Unidad Educativa Dr. Gonzalo Abad Grijalva, de la ciudad de Piñas, en el año lectivo 2012-2013. - Cueva Andrade, Mercedes Katherine (2013)
The incidence of reading comprehension in the academic performance of students in the seventh year of EGB, is the central concern of this research study, whose central hypothesis estimated that the low level of reading comprehension of students affects the poor academic performance same.